THE EFFECT OF INTELLECTUAL CAPITAL AND GOOD CORPORATE GOVERNANCE ON FINANCIAL PERFORMANCE IN BANKING SECTOR REGISTERED IN INDONESIA STOCK EXCHANGE WITH COMPETITIVE ADVANTAGE AS INTERVENING VARIABLES FOR 2016-2019 - Novi Crisnandani; Ika Yustina Rahmawati; Naelati Tubastuvi; Totok Haryanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this study is to obtain empirical evidence of the role of Competitive Advantage in mediating the relationship between Intellectual Capital and Good Corporate Governance and Financial Performance. The population of this study is the banking sector companies listed on the Indonesia Stock Exchange (BEI) 2016-2019. The method of determining the sample using a purposive sampling technique. The number of samples obtained was 31 companies with a total of 124 observations. Based on the research results, it was found that the variable that had a direct influence on the Competitive Advantage was the Good Corporate Governance variable, while the Intellectual Capital variable did not have a direct effect. Meanwhile, the variables that have a direct influence on financial performance are the variables of Good Corporate Governance and Competitive Advantage. Based on the results of the analysis, it was also found that Competitive Advantage was not able to mediate the relationship between Intellectual Capital and Financial Performance but was able to mediate the relationship between Good Corporate Governance and Financial Performance. Keywords: Intellectual Capital, Good Corporate Governance, Competitive Advantage, Financial Performance